Clinico-Therapeutic Studies on Canine Pyoderma - Udayasree V J (Department of clinical medicine, College of Veterinary and Animal Sciences, 2004)
Prevalence of pyoderma was studied among the dogs presented with dermatological problems at the University Veterinary Hospitals, Mannuthy and Kokkalai during the period from May 2003 to April 2004. Among the 409 dermatological problems in canines, bacterial dermatitis was 12.71 per cent (52 . cases). Incidence of surface pyoderma, superficial pyoderma and deep pyoderma were 26.92,53.85 and 19.23 per cent respectively. Surface pyoderma were more in age groups between one and four years, superficial pyoderma were more in age group below six months and deep pyoderma was more in age group between six and 12 months. The most frequent lesions were pustules, papules, erythema, alopecia and epidermal collarette and distributed mostly on axilla, abdomen, flank and trunk region. A significant increase in eosinophil count, with decrease in monocytic count and serum zinc level was observed in the affected dogs. Out of the 26 bacterial isolates 21 (80.77 per cent) were gram positive and five (19.23 per cent) were gram negative. Staphylococcus intermedius (12) was the major pathogen isolated from canine pyoderma followed by Staphylococcus aureus (8), Staphylococcus epidermidis (1), Escherichia coli (3), Pseudomonas aeruginosa (1) and Klebsiella spp. (1). Ciprofloxacin, enrofloxacin and erythromycin were found to be the most effective antibiotics against bacterial isolates of canine pyoderma, ampicillin and cloxacillin the least effective.